GENERALIZED (2m, m)−RECTANGULAR BANDS OF TYPE (3, 2) - Miovska, Valentina; Dimovski, Dončo (Matematichki Bilten, 2010)
Notions of generalized left-zero and right-zero \((2m,m)\)-semigroups of type \((3,2)\) are introduced, and so is the notion of generalized \((2m,m)\)-rectangular band of type \((3,2)\). Characterizations of generalized left-zero and right-zero \((2m,m)\)-semigroups of type \((3,2)\) and generalized \((2m,m)\)-rectangular band of type \((3,2)\) are given.